Internal audit and its role in achieving financial sustainability in self-financing units /case study - Alhabow, Abdalsalam H.M.; Hamoudi, Kobra M. T.; Alshaikhli, Saja Akram Abdulrazzaq (CV. Bimbingan Belajar Assyfa, 2023)
The aim of this research is to demonstrate the role of internal audit activity in achieving financial sustainability in self-financing units, and to achieve the objectives of the research and test its hypotheses, we conducted a case study in municipal institutions in Nineveh Governorate. One of the most important findings of the study that the researchers reached was the weak role of internal audit in achieving financial sustainability, the lack of adoption of modern internal audit objectives, and the lack of a clear program for internal audit prepared according to sustainability. The study concluded with a number of recommendations, the most important of which are: Activating the internal audit advisory services with regard to the financial sustainability of the unit, directing its expenditures and maximizing its revenues, and the internal audit should measure the financial sustainability of the financial reporting information through specific quantitative measures.